2002
DOI: 10.2533/000942902777680162
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Assembly and Self-Assembly: Molecular Nanoscience for Future Technologies

Abstract: In this review the emerging science of single molecules is discussed from the perspective of nanoscale molecular functions and devices. New methods for the controlled assembly of well-defined molecular nanostructures are presented: self assembly and single molecular positioning. The observation and selective modification of conformation, electronics, and molecular mechanics of individual molecules and molecular assemblies by scanning probes are demonstrated. To complement this scientific review, some of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
(39 reference statements)
0
12
0
1
Order By: Relevance
“…Owing to their unique optical and electrical properties, QDs have been extensively used in microelectronics and biomedical and biological research (De Wild et al, 2003). In the past few decades, QDs have been used in a number of commercial applications including optoelectronics, quantum computing, solar cells, light emitting devices, and security inks (Harrison et al, 2000;Wu et al, 2004;Zhao et al, 2006;Hetsch et al, 2011;Qian et al, 2011).…”
Section: Application Of Quantum Dotsmentioning
confidence: 99%
See 4 more Smart Citations
“…Owing to their unique optical and electrical properties, QDs have been extensively used in microelectronics and biomedical and biological research (De Wild et al, 2003). In the past few decades, QDs have been used in a number of commercial applications including optoelectronics, quantum computing, solar cells, light emitting devices, and security inks (Harrison et al, 2000;Wu et al, 2004;Zhao et al, 2006;Hetsch et al, 2011;Qian et al, 2011).…”
Section: Application Of Quantum Dotsmentioning
confidence: 99%
“…Studying the mechanisms of toxicity of NPs will provide a basis for classifying materials for regulatory purposes and prescribing strategies for risk management (Thomas et al, 2006). Cadmium-based QDs are widely used in microelectronics and biomedical research and offer great potential in medical imaging, diagnosis, and therapeutic targeting (De Wild et al, 2003;Gao et al, 2004;Jamieson et al, 2007). Even though previous studies have reported the toxicity of these NPs, the mechanisms related to their toxic effects in cell lines and in animals are still unclear (Wu et al, 2003;Derfus et al, 2004;Kirchner et al, 2005;Samia et al, 2006;Lovric et al, 2005;Hardman, 2006).…”
Section: Rationales For the Researchmentioning
confidence: 99%
See 3 more Smart Citations